2005
DOI: 10.1002/yea.1237
|View full text |Cite
|
Sign up to set email alerts
|

Specific aspartate residues in FET3 control high‐affinity iron transport in Saccharomyces cerevisiae

Abstract: Site-directed mutagenesis was performed on a set of six aspartate residues of Fet3, the multicopper ferroxidase involved in high-affinity iron transport in Saccharomyces cerevisiae, in order to comprehend the molecular determinants of the protein function. Asp312, Asp315, Asp319 and Asp320 were predicted by homology modelling to be located in a negatively charged surface-exposed loop of the protein. Other two aspartate residues (Asp278 and Asp279) are placed close to the type 1 copperand iron-binding sites, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Although the exact molecular mechanism by which IMAs regulate Fe uptake genes remain to be elucidated, binding to Fe 2+ may control the stability of IMA peptides and thereby regulate Fe uptake. Negatively charged residues such as aspartate participate in the Fe coordination in numerous proteins 52,53,54 . Consistent with the putative metal-binding properties of the Asp stretch in the IMA motif, we showed that IMA peptides can bind Fe 2+ and other metals.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact molecular mechanism by which IMAs regulate Fe uptake genes remain to be elucidated, binding to Fe 2+ may control the stability of IMA peptides and thereby regulate Fe uptake. Negatively charged residues such as aspartate participate in the Fe coordination in numerous proteins 52,53,54 . Consistent with the putative metal-binding properties of the Asp stretch in the IMA motif, we showed that IMA peptides can bind Fe 2+ and other metals.…”
Section: Discussionmentioning
confidence: 99%
“…However, all of these residues are part of the water-accessible (Connolly) surface of the protein, ensuring access from bulk solvent. A previous modeling study led to the proposal that D319 and D320 are part of a solvent-exposed, negative patch involved in Fe binding (62). In fact, these residues are part of an electrostatic ''zipper'' where the two carboxylate side chains are in salt bridges with the side chains of R463 and R427, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Based on site-directed mutagenesis of the S. cerevisae FET3 protein, previous research identified D319 and D320 to be critical for the growth of yeast under Fe-deficient conditions. In particular, mutation of D320 abrogated the FET3-dependent Fe uptake function (Bonaccorsi di Patti et al, 2005;Quintanar et al, 2007). Kinetic studies of mutations of the E185, D283, and D409 residues, respectively, showed their important role in Fe(II) oxidation (Quintanar et al, 2007).…”
Section: In Silico Identification Of Fet3 Homologs In Arabidopsis Thalianamentioning
confidence: 99%
“…S. cerevisiae ferroxidase FET3(Askwith et al, 1994) contains essential aspartic residues which play an important role in Fe(II) oxidation(Bonaccorsi di Patti et al, 2005;Quintanar et al, 2007).Frontiers in Plant Science | www.frontiersin.org…”
mentioning
confidence: 99%